(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
In this paper thesis describes an experimental investigation of magnesium based cement mortar which consists of fly ash, magnesium oxide (MgO), magnesium Phosphate (MgPO4) and Phosphate tailings. This magnesia based cements are emerged as a viable alternative to Portland cement, with both technical and sustainability advantages. This study aims to use the mixture of cement, fly ash and magnesia. The major drawback of delayed setting time can be eliminated with the use of magnesia based cement. Hence, in this study different admixtures such as magnesium oxide, magnesium phosphate, phosphate tailings are attempted. Initial and final setting time of plain cement, fly ash cement and magnesia based cement are determined and found that the small dosage of magnesium compound reduced the setting time. Further, magnesia based cements are reported to be used along with sea water without much negative effect. In view of all these, this study proposed a magnesia based cement as an alternative for conventional Portland cement. Industrial wastes such as fly ash, and phosphate tailings are used in this study.